2011
DOI: 10.1590/s0001-37652011000200028
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of cucumber and lettuce intercropping under greenhouse in the winter-spring

Abstract: The economical analysis complements the evaluation of the intercrop systems efficiency, considering besides the physical production of crops, the price of products according to their quality classification and time of the year. Intercropping systems of lettuce and cucumber in two plant populations under greenhouse were economically evaluated in winter-spring, in Jaboticabal City, São Paulo State, Brazil. The total operating cost (TOC) of cucumber and lettuce as sole crop and intercropping were estimated, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
2
9
0
2
Order By: Relevance
“…However, later transplants led to significantly reduced lettuce weight; when lettuce was transplanted 30 d after the tomato plants, the lettuce plants were etiolated and had no market value. Similar results were observed by Rezende et al (2011), who evaluated the effect of the transplant time of lettuce intercropped with cucumber. The authors observed that the intercrop was only feasible when the lettuce was transplanted on the same day as the cucumber as late lettuce transplanting caused a strong decrease in accumulated weight and commercial characteristics.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, later transplants led to significantly reduced lettuce weight; when lettuce was transplanted 30 d after the tomato plants, the lettuce plants were etiolated and had no market value. Similar results were observed by Rezende et al (2011), who evaluated the effect of the transplant time of lettuce intercropped with cucumber. The authors observed that the intercrop was only feasible when the lettuce was transplanted on the same day as the cucumber as late lettuce transplanting caused a strong decrease in accumulated weight and commercial characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…However, few studies have been conducted with vegetables in protected environments. Cecílio Filho et al ( , 2013, Rezende et al (2011), and Tringovska et al (2015) tested the agronomic and economic feasibility of intercropping tomato and lettuce and intercropping cucumber and lettuce in protected cultivation.…”
mentioning
confidence: 99%
“…54542.00 for single season. Rezende et al (2011) and Sreedhara et al (2013) had also similar observations regarding expenditure incurred on fixed component, thus showing slow response of growers for adoption of this technology. However, with the involvement of Government in boosting this technology financially, the initial capital investment with respect to structure came down to Rs.…”
Section: Resultsmentioning
confidence: 71%
“…To obtain good results from intercropping, various production factors that have already been properly studied in monocultures need to be reevaluated. Even in cucumber and lettuce intercropping, which has proven agroeconomic viability (REZENDE et al, 2011), simply changing the cultivar (PORTO et al, 2011;CECÍLIO FILHO et al, 2015) or cropping season (CECÍLIO FILHO et al, 2011) can affect overall viability, including leading to total failure (REZENDE et al, 2010).…”
Section: Introductionmentioning
confidence: 99%